PENGARUH KEPEMIMPINAN DAN KOMITMEN ORGANISASI TERHADAP KEPUASAN KERJA DIMEDIASI BUDAYA ORGANISASI - Setiyani Budi Susilowati (Universitas Muhammadiyah Surakarta, 2014)
This research aims to analyze the impact of leadership behavior on job satisfaction, organizational commitment analyze the effect on job satisfaction, analyzing organizational culture affects the relationship between leadership behavior and job satisfaction, analyzing organizational culture moderates the relationship of organizational commitment and job satisfaction. The populations in this study were all employees BBRSBD Prof. Soeharso Surakarta, and the population size is equal to 201 employees. In this study a sample of 134 respondents was taken. Sampling technique in this research is to use a proportional random sampling. The results showed there are signiﬁcant effect of leadership behavior on job satisfaction. Moderate the inﬂuence of organizational culture on the leadership behavior and job satisfaction is positively signiﬁcant. Moderate the inﬂuence of organizational culture on organizational commitment and job satisfaction are positively signiﬁcant.